2016
DOI: 10.1055/s-0042-113460
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Streptozotocin-Induced Diabetes on Proliferation and Differentiation Abilities of Mesenchymal Stem Cells Derived from Subcutaneous and Visceral Adipose Tissues

Abstract: Accumulated evidence indicates that there are intrinsic differences between adipose tissue-derived stem cells (ASCs) obtained from different body fat depots. Here, we compared the proliferation and multipotency of subcutaneous ASCs (SC-ASCs) and epididymal ASCs (ED-ASCs) before and after induction of diabetes by streptozotocin. The adipogenic and osteogenic abilities of rat SC-ASCs and ED-ASCs were evaluated using Oil Red O and Alizarin Red staining, respectively. The expression of adipocyte (PPAR-γ, LPL) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…This was in contrast to multiple reports that showed GMSCs to have a higher proliferation compared to PDLSCs [ 29 ][ 32 ][ 33 ][ 34 ]. This pattern of proliferation described in the diabetic patient was in contrast to previous reports that demonstrated that early after the induction of diabetes with streptozotocin, the proliferative capacity of bone marrow-derived stem cells increased [ 23 ]. The inclusion of a greater number of diabetics enrolled in our study in contrast to using diabetes-induced models may help explain this result.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This was in contrast to multiple reports that showed GMSCs to have a higher proliferation compared to PDLSCs [ 29 ][ 32 ][ 33 ][ 34 ]. This pattern of proliferation described in the diabetic patient was in contrast to previous reports that demonstrated that early after the induction of diabetes with streptozotocin, the proliferative capacity of bone marrow-derived stem cells increased [ 23 ]. The inclusion of a greater number of diabetics enrolled in our study in contrast to using diabetes-induced models may help explain this result.…”
Section: Discussioncontrasting
confidence: 99%
“…This is especially true for a disease like diabetes. The majority of mesenchymal stem cells previously studied for therapeutic purposes have been from sources like bone marrow and adipose tissue [ 23 ][ 28 ]. Both, PDLSCs and GSCs demonstrated promising potential for use in tissue regeneration [ 29 ][ 30 ][ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical treatment of diabetes with insulin is associated with weight gain and increased adiposity (Purnell & Weyer, ), and insulin promotes adipogenesis and lipogenesis in cell culture. However, similar to ASCs from insulin‐resistant individuals, cultured scASCs from rats with streptozotocin‐induced Type 1 (insulin‐dependent) diabetes exhibited a blunted adipogenic response in culture (Ghorbani et al, ), demonstrating that Type 1 diabetes or chronic hyperglycemia may induce fundamental changes in the insulin signaling of ASCs. Of note, the modified insulin analog detemir, which does not affect body weight, was also correspondingly shown to be less adipogenic than standard insulin when added to cultures of human scASCs and omASCs (Cignarelli et al, ).…”
Section: Overview Of Recently Published Work In Ascsmentioning
confidence: 99%
“…Myo broblasts derived from other cells have been shown to produce more contractile activity than proto-myo broblasts in the absence of changes in the expression of other contractile proteins [10] .Therefore, a number of studies have attempted to use MSC and other cells as the therapeutic options for diabetic wound repair. Most mesenchymal stem cells used in previous studies for therapeutic purposes were derived from bone marrow and adipose tissue [11] [12] ,However, the di culty of sampling and the degree of damage to the host greatly limit its clinical application. Thus, it makes sense to nd a better source of suitable cells.…”
Section: Introductionmentioning
confidence: 99%